2019
DOI: 10.21106/ijma.263
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality at the Dori Regional Hospital in Northern Burkina Faso, 2014-2016

Abstract: Background: Maternal mortality is of considerable magnitude. It is particularly relevant to developing countries, including those in Sub-Saharan Africa. The aim of this work was to study the cases of maternal deaths in the Dori Regional Hospital, Burkina Faso in the Sahel region, by analyzing the epidemiological aspects of these deaths in order to guide decision-making. Methods: This was a descriptive cross-sectional study which spanned the period from January 1, 2014 to December 31, 2016. Cases of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…The direct and indirect contribution of anemia to maternal death or near-misses has been demonstrated previously in low-resource settings, but also alongside additional large dataset analyses showing similar findings in highresource settings including Canada, Scotland and France. 16, [21][22][23][24][25][26][27][28][29][30] Our study further demonstrated the role of anemia as an independent risk factor for higher rates of blood transfusion, PPH, need for hysterectomy, preeclampsia, cesarean delivery, and infectious morbidity, consistent with previous publications. 3,4,9,16,23,26,29,31 Women with anemia are less tolerant of greater volumes of blood loss compared to those without due to lower reserves of red blood cells, thus increasing their risks for transfusion, hysterectomy, and ICU admission as seen in our study and previous studies.…”
Section: Resultssupporting
confidence: 86%
“…The direct and indirect contribution of anemia to maternal death or near-misses has been demonstrated previously in low-resource settings, but also alongside additional large dataset analyses showing similar findings in highresource settings including Canada, Scotland and France. 16, [21][22][23][24][25][26][27][28][29][30] Our study further demonstrated the role of anemia as an independent risk factor for higher rates of blood transfusion, PPH, need for hysterectomy, preeclampsia, cesarean delivery, and infectious morbidity, consistent with previous publications. 3,4,9,16,23,26,29,31 Women with anemia are less tolerant of greater volumes of blood loss compared to those without due to lower reserves of red blood cells, thus increasing their risks for transfusion, hysterectomy, and ICU admission as seen in our study and previous studies.…”
Section: Resultssupporting
confidence: 86%
“…The other studies were: case-control (n = 1) [ 38 ], Confidential Enquiries into Maternal Deaths (CEMD) or Maternal Death Surveillance and Response (MDSR) audits (n = 4) [ 39 - 42 ], cross-sectional facility and community surveys (n = 4) [ 43 - 46 ], prospective facility and community studies (n = 2) [ 47 , 48 ], Reproductive Age Mortality Study (RAMOS) (n = 2) [ 49 , 50 ], pre and post evaluation (n = 1) [ 51 ], and step-wedge randomised controlled trials (RCT) (n = 1) [ 52 ]. The methods of assigning the causes of death were: study expert panels (n = 21) [ 17 , 18 , 21 , 22 , 24 , 26 , 28 , 29 , 33 - 35 , 37 , 39 , 43 - 46 , 48 - 50 , 52 ], facility/MDSR audit teams (n = 8) [ 16 , 23 , 25 , 31 , 41 , 42 , 51 , 53 ], routine clinical assessments (n = 5) [ 19 , 20 , 27 , 30 , 32 ], physician verbal autopsy coders (n = 1) [ 47 ], and not stated (n = 3) [ 15 , 36 , 38 ]. South Africa contributed 21% of the deaths from 2 studies [ 22 , 41 ], Nigeria 18% from 13 studies [ 15 , 21 , 23 - 25 , 28 - 31 , 35 , 37 , 46 , 48 ], Tanzania 15% from 3 studies [ 16 , 18 , 39 ], and Zimbabwe 9% from 2 studies [ 20 , 42…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of included articles by country was as follows:, Algeria [60], Benin [78], Burkina Faso [122,143], Cameroon [99,133], Democratic Republic of Congo [55,82], Egypt [105], Eritrea [102], Ethiopia [57,62,71,72,74,86,130,131], Ghana [49,52,53,58,69,141], Guinea-Bissau [76], Kenya [63,91,110,123,142,145], Madagascar [79], Malawi [80,83,100,126,140], Morocco [44], Mozambique [59], Nigeria [42,43,45,47,48,54,56,65,67,89,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%